2010
DOI: 10.1016/j.commatsci.2009.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of elastic properties of cement pastes at early ages

Abstract: Cementitious materials are known to be sensitive to cracking at early ages. During the first days which follow the contact between water and cement, the system is continuously evolving, as its mechanical characteristics follow a rapid rate of change and the material is prone to cracking. One of the parameters that highly influence the behavior of the material at early ages is the Young's modulus. Analytical calculations, based on existing homogenization models and finite element calculations, applied on a disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(41 citation statements)
references
References 25 publications
2
34
0
Order By: Relevance
“…The self consistent scheme is well-suited to capture the solid percolation threshold of the REV drawn at level II [6]. However, as it was pointed out by different authors for low water-to-cement ratios, additional precautions must be taken into account to ensure the accuracy of the prediction of the solid percolation threshold [6,14,15,51]. In particular, Sanahuja et al [15] considered LD C-S-H particles as platelets (oblates) with an aspect ratio varying in function of the water-to-cement ratio.…”
Section: Localizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The self consistent scheme is well-suited to capture the solid percolation threshold of the REV drawn at level II [6]. However, as it was pointed out by different authors for low water-to-cement ratios, additional precautions must be taken into account to ensure the accuracy of the prediction of the solid percolation threshold [6,14,15,51]. In particular, Sanahuja et al [15] considered LD C-S-H particles as platelets (oblates) with an aspect ratio varying in function of the water-to-cement ratio.…”
Section: Localizationmentioning
confidence: 99%
“…The extension of these models to take into account the poroelastic behavior of concrete materials [1,9,10] introduced several model applications [11][12][13][14]. At early-age, the microstructure evolves due to the hydration of anhydrous cement particles and additional chemical reactions.…”
Section: Introductionmentioning
confidence: 99%
“…The Young's modulus of ∼ 5 GPa corresponds to the stiffness of nylon,[117] whereas the Young's modulus of ∼ 20 GPa corresponds to the stiffness of concrete. [118] Similar studies can be performed for the bending deformations of the C 60 ·TMB crystals, calculation of their shear modulus, and so forth. Another possible application of MBN Explorer could be to study the transitions between different isomeric states of the composite crystals exhibiting deformation and to investigate the phase transitions between different crystalline forms under the variation of temperature, pressure, and anisotropic forces applied to the system.…”
Section: Resultsmentioning
confidence: 99%
“…As would be expected, the lower w/c mixtures require less time to achieve percolation (set), due to their reduced initial particle spacing [34]. Several recent studies have demonstrated correlation between experimental measurements of setting, such as ultrasonics and needle penetration, and various model-based measurements of solids percolation [13,14,16,17]. Thus, it is important for cement hydration and microstructural models first to provide a measure of solids percolation and then to duplicate these commonly observed influences of w/c on setting.…”
Section: Critical Observationsmentioning
confidence: 96%
“…While isothermal calorimetry monitors the rate of chemical reactions in a cementitious system, the actual hardening of the cement paste microstructure is a physical process that depends on building ''bridges'' between the reacting cement particles [12][13][14][15][16][17]. This percolation of a ''solid'' backbone across the 3-D volume of cement paste is typically assessed using a penetration test such as that described in the ASTM C 191 standard test methods for time of setting of hydraulic cement by Vicat needle [10].…”
Section: Vicat Needle Penetration-percolation Of Solidsmentioning
confidence: 99%